A Literatur Review Green Energy Pada Pemancar Sistem Komunikasi Seluler - Kardiyasa, Komang Agus Putra; Gunantara, Nyoman (Majalah Ilmiah Teknologi Elektro, 2023)
The number of users and the frequency of use of telecommunications systems are increasing rapidly and causing a greater demand for energy use. Based on many studies conducted by various network operators, that the largest energy consumption and the most impact on the environment is wireless networks from both the recipient and sender sides. The amount of CO2 emissions is increasing in communication systems, equivalent to the increase in cellular consumers. And it is also observed that the current wireless network is not energy efficient, especially the Base Station (BTS). The rapid and alarming growth in wireless network users is forcing us to use higher mobile broadband data rates. The need for an urgent network architecture restructuring in order to provide good service but still be environmentally friendly. In this article, we will discuss several innovative methods to increase the energy efficiency of wireless networks and develop solutions that reduce operating costs and the impact on the environment.